GEODYNAMIC STATE OF THE TRANSCARPATHIAN INNER TROUGH BASED ON THE RESULTS OF DEFORMATION MONITORING OBSERVATIONS IN THE REGION - IHNATYSHYN, Vasyl; MALYTSKYY, Dmytro; IZHAK, Tibor; MOLNAR, Stefan; IHNATYSHYN, Monika; IHNATYSHYN, Adalbert (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The relevance of the research is determined by the gradual increase in local seismicity in the region, which occupies a peculiar geographical location, through which oil, gas and product pipelines pass, and in which critical infrastructure facilities are located that may be affected by the underground natural disaster. It is important to have information on the movements of the upper layers of the Earth's crust, their kinematics and dynamics, which significantly affect the stress-strain state of rocks and the release of energy from geomechanic processes. It is also necessary to investigate the influence of the region's geodynamics on the discharge of the stress-strain state of rocks. Methods. The research methodology is to construct time-dependent crustal displacements and compare velocities and accelerations of crustal movements in the intervals of anomalous modern lateral movements of the Earth's crust. The velocities and accelerations of crustal movements are calculated, the kinematics of movements and seismicity of the region are compared. Correlation analysis of the observed series is applied. To solve the tasks, we used the results of observations of horizontal crustal movements in the Oașh deep-seated fault area using a quartz strain gauge with a base of 24.5 m mounted in the adit of the Korolevo urban-type settlement. The seismic data were obtained using digital seismometers operating at the monitoring geophysical station of the Seismicity Department of the Carpathian region of S.I. Subbotin Institute of Geophysics of the National Academy of Sciences of Ukraine. Results. The article discusses the geodynamics of the Transcarpathian Inner Trough based on observations of modern lateral movements of the Earth's crust in the Oașh deep-seated fault area, which in 2021 were represented by rock extensions of +12.61x10-7. The physical parameters of geomotion in the region were calculated, the spatiotemporal distribution of local seismicity was established, and the relationship between seismic and geodynamic states in Transcarpathia in 2021 was studied. The variations of displacements of the upper layers of the Earth's crust over the entire period of deformation monitoring observations in Korolevo urban-type settlement (1999–2021) and the temporal distribution of local underground shocks were studied.   Conclusions. The analysis of the spatio-temporal distribution of local seismicity and modern lateral movements of the Earth's crust over the entire period of deformation monitoring observations in the Oașh deep-seated fault area has indicated an increase in the seismicity of the region in the intervals of intense crustal movements and the presence of periods of crustal movement fluctuations for 12 years: familiar variable processes (expansion and contraction of rocks, the total magnitude of displacement fluctuations in the region of zero movements) were detected for 2–3 years. The most relevant and important are the periods of 9–10 years following these calm intervals, since during this time earthquakes are recorded and their frequency is also found to be increasing. The intensification of seismicity in the region is observed against the background of general rock extension, which occurs due to the steady age-related crustal movements. At the present stage, the current crustal movements are in a state of rock expansion, and if this trend does not change, an increase in seismicity in the region should be expected.
Keywords: deformation gauge; modern lateral movements of the Earth's crust; crustal velocity; acceleration of rock motion; geodynamic state; earthquakes; local seismicity; seismotectonic processes; Oașh deep-seated fault